A benchmark for comparison of cell tracking algorithms - Mas̆ka, Martin; Ulman, Vladimír; Svoboda, David; Matula, Pavel; Matula, Petr; Ederra, Cristina; Urbiola, Ainhoa; España, Tomás; Venkatesan, Subramanian; Balak, Deepak M. W.; Karas, Pavel; Bolcková, Tereza; et al. (Bioinformatics, 2014)
Abstract. Motivation: Automatic tracking of cells in multidimensional time-lapse fluorescence microscopy is an important task in many biomedical applications.
Gesehen am 17.08.2020